2021
DOI: 10.1029/2021wr030391
|View full text |Cite
|
Sign up to set email alerts
|

The Four Ways to Consider Measurement Noise in Bayesian Model Selection—And Which One to Choose

Abstract: Models are used to predict and/or investigate and explain phenomena in nature. Often, many hypotheses exist for these two tasks. Naturally, the question arises, which of the competing modeling approaches predicts or explains nature best. Bayesian model selection (BMS, e.g., Wasserman, 2000) is a statistical method that uses observed data to select between competing models. BMS is settled in a rigorous probabilistic framework and follows the scheme of Bayesian updating: A prior belief about the plausibility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Discharge records are subject to uncertainty and its estimation can reduce economic costs of water management decisions (H. McMillan et al., 2017) and allows robust research conclusions to be drawn, as demonstrated in data assimilation (Burgers et al., 1998), regionalization (Westerberg et al., 2016), and Bayesian model selection (Reuschen et al., 2021). Discharge time series are usually obtained by relating continuously measured river stage to discharge through so‐called rating curves.…”
Section: Introduction and Scopementioning
confidence: 99%
“…Discharge records are subject to uncertainty and its estimation can reduce economic costs of water management decisions (H. McMillan et al., 2017) and allows robust research conclusions to be drawn, as demonstrated in data assimilation (Burgers et al., 1998), regionalization (Westerberg et al., 2016), and Bayesian model selection (Reuschen et al., 2021). Discharge time series are usually obtained by relating continuously measured river stage to discharge through so‐called rating curves.…”
Section: Introduction and Scopementioning
confidence: 99%
“…Te posterior probabilities of each model can be used as the weights for inference, and the weighted average of the models of interest can be obtained to determine the BMA [39][40][41][42][43]. Te BMA modeling approach is based on a large model space, but performing scientifc sampling in the model space to identify models with high posterior probabilities remains a challenge in applying BMA.…”
Section: Bayesian Model Averagingmentioning
confidence: 99%
“…In BMJ, N d realizations from the parameter prior of each data-generating model M j are sampled and evaluated in the model. Noise is then added to each data set to account for the measurement error associated to real observations (Reuschen et al, 2021).…”
Section: Bayesian Justifiability Analysismentioning
confidence: 99%
“…If one had an infinite number of model realizations, the geostatistical model would be able to reproduce data generated from itself perfectly. To properly account for measurement noise in this synthetic setup for BMS and BMJ analysis, noise was added to the synthetic data set, to account for measurement error (Reuschen et al, 2021). For the noise, we consider a standard deviation of h error = 0.06m and c error = 0.06 + 0.2c o ,…”
Section: Synthetic Setupmentioning
confidence: 99%
See 1 more Smart Citation